The Town Mouse and The Country Mouse - Retold by Davidson, Susanna (London Usborne Publishing Ltd, 2007)
When the town mouse and the country mouse visit each other, they find they prefer very different ways of life.
Include Color Illustration
Keywords: Fables -- Conduct of life -- Folklore